Recent advancement in bimetallic metal organic frameworks (M′MOFs): synthetic challenges and applications. Issue 12 (13th May 2022) - Ahmed, Manan
Abstract : This review aims to highlight the synthetic challenges for the preparation of bimetallic MOFs (M′MOFs) and their gas adsorption, heterogeneous catalysis, photocatalysis and luminescence properties. Abstract : Metal–organic frameworks (MOFs) are a burgeoning research field and have received increasing interest in recent years due to their inherent advantages of inorganic metal ions, range of organic linkers, tunable porosity and diverse functionality. During the last decades, these materials have been found in several applications and have been applied to gas storage, separation, photocatalysis, catalysis, luminescence, and sensing. They have also been applied to a range of biological uses such as drug delivery. Therefore, in order to design novel and new MOFs with desired functionalities, a fundamental concern is to achieve a basic understanding of the relationship between molecular parameters and structures, preferred adsorption sites and properties. In this regard, the stepwise construction of MOFs provides the opportunity to access this goal. Most of the studies on the characteristic properties of MOFs were based on the use of materials containing a single metal ion in the framework. The past decade has witnessed these remarkable advances and vibrant research areas; however, nowadays, the most recent trend in the field of MOFs is to obtain new functional MOFs having two different metal ions in their framework, which is a relatively new concept. The bimetallic MOFs (M′MOFs) possess a wide array of potential properties compared to the single metal MOFs. Thereby, this review aims to highlight recent research progress of M′MOFs in the area of gas adsorption, heterogeneous catalysis, photocatalysis and luminescence applications. Particular emphasis is given to providing the different examples of synthetic routes and the influence of mixed metals to well understand the usefulness of M′MOFs.